(untitled) (Global Journals of Research in Engineering, 2022)
This paper established the general energy efficiency equations of both dual axis and single axes vertical and horizontal single axis solar tracking systems based on a theoretical approach underlain substantially by the principle that only the normal component of solar radiation is mainly converted into electrical energy The energy efficiency equations as comparative energy gain factor were established by comparing the tracking systems dual and single and static fixed photovoltaic cell arrays one to each other Dual axis to Static Dual axis to Vertical Single axis horizontal tracking of sun position Dual axis to Horizontal Single axis vertical tracking of sun position and by inference single axes to static cell arrays The study did not cover neither the numerous design models of solar tracking systems that involve different energy consumption due to different apparatus and mechanisms and different costs nor the weather conditions impacts on their efficiencies